PENERAPAN TEOREMA BAYES DALAM MEMPREDIKSI BAYI TERLAHIR CACAT - Desi Ratnasari; Nelly Astuti Hasibuan (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2017)
The development of computer-based medical systems has increased considerably today. One of the health problems that often interfere with pregnant women is that the risk of a baby born with a disability is often overlooked because most people do not understand that a baby can be born with a disability and assume that all babies have a disability after being born not before birth, but actually born babies are quite dangerous and can result in death. This study aims to build an expert-based application that can be used to make early predictions of birth defects. This expert-based application, which mimics the workings of an expert or physician in analyzing the symptoms. Type Inference engine (machine reasoning) used in the research Bayes Theorem is a theory to generate parameter estimation by combining information from samples and other information that has been available previously.